Show that if $P$ is a (hermitian) projection operator, so are (a) $1-P$ and (b) $$ U^{+}PU $$ for any operator $U$

Definition of projection operator is $P\circ P = P$, for (a) you can simply expand $(1-P)\circ (1-P)$ and find it holds true. You have to define the notation $U^+$ to get an answer for (b).

October 11, 2014 00:50 AM

$$\begin{align} (1-P)^2(x) &=(1-P) \circ ((1-P)(x)) \\ \implies (1-P)^2(x) &=(1-P) \circ (x-P(x)) \\ \implies (1-P)^2(x) &=(x-P(x))-(P(x)-P^2(x)) \\ \end{align}$$ Now using the fact that P is a projection operator, i.e. $P^2=P$, we get: $$ \begin{align} \implies (1-P)^2(x)&=(1-P)(x)-(P(x)-P(x)) \\ \implies (1-P)^2(x)&=(1-P)(x)\\ \end{align} $$

Hence we get $(1-P)^2=(1-P)$, which implies $(1-P)$ is a projection operator.

October 20, 2019 05:11 AM

- Serverfault Help
- Superuser Help
- Ubuntu Help
- Webapps Help
- Webmasters Help
- Programmers Help
- Dba Help
- Drupal Help
- Wordpress Help
- Magento Help
- Joomla Help
- Android Help
- Apple Help
- Game Help
- Gaming Help
- Blender Help
- Ux Help
- Cooking Help
- Photo Help
- Stats Help
- Math Help
- Diy Help
- Gis Help
- Tex Help
- Meta Help
- Electronics Help
- Stackoverflow Help
- Bitcoin Help
- Ethereum Help